Social assistance - no, thanks? Empirical amalysis of non-take-up in Austria 2003 - Michael Fuchs (University of Essex, Institute for Social and Economic Research (ISER), 2007)
Based on the comparison of detailed micro-data (EU-SILC), official figures on recipients and expenditure as well as potential entitlements simulated with the tax/benefit microsimulation model EUROMOD, the paper estimates the size of non-take-up of monetary social assistance benefits in Austria in 2003. To account for likely measurement errors both in the reported income data as well as in the simulation of household needs, participation rates are calculated for various scenarios of the underlying parameters. I find that more than half of all households potentially entitled to the benefit do not claim. The determinants of non-take-up analysed in different regression models controlling for possible endogeneity of independent variables – significant higher participation rates inter alia in case of higher amounts entitled to, a non-employed head, living in Vienna – confirm hypotheses derived from theoretical models of take-up related to pecuniary determinants, information and administration costs as well as psychological costs.
Keywords: D31; H31; H53; I38; 330; Austria; take-up; social assistance; microsimulation; Sozialhilfe; Entscheidung; Privater Haushalt; Simulation; Schätzung; Österreich